2017
DOI: 10.1371/journal.pbio.2000949
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas lineage allocation and specification are regulated by sphingosine-1-phosphate signalling

Abstract: During development, progenitor expansion, lineage allocation, and implementation of differentiation programs need to be tightly coordinated so that different cell types are generated in the correct numbers for appropriate tissue size and function. Pancreatic dysfunction results in some of the most debilitating and fatal diseases, including pancreatic cancer and diabetes. Several transcription factors regulating pancreas lineage specification have been identified, and Notch signalling has been implicated in lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 78 publications
0
36
0
Order By: Relevance
“…The complex interactions of sphingolipids with nuclear gene regulation suggest close links between these pathways, but detailed understanding is missing. The ability of the sphingosine mimetic drug FTY720/fingolimod to modulate gene expression in neurons and astrocytes [38,39] is probably due in large part to the links observed between S1P receptor signaling and the activities of crucial transcription factors including NF-κB, Yin-Yang-1, or Notch [71][72][73][74][75]. However, the inhibition of class I HDACs by FTY720 / FTY720P must also be considered a potential mechanism [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The complex interactions of sphingolipids with nuclear gene regulation suggest close links between these pathways, but detailed understanding is missing. The ability of the sphingosine mimetic drug FTY720/fingolimod to modulate gene expression in neurons and astrocytes [38,39] is probably due in large part to the links observed between S1P receptor signaling and the activities of crucial transcription factors including NF-κB, Yin-Yang-1, or Notch [71][72][73][74][75]. However, the inhibition of class I HDACs by FTY720 / FTY720P must also be considered a potential mechanism [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…A high level of Notch signaling represses Ngn3 expression but enhances ductal cell differentiation. Wnt, sphingosine-1-phosphate (S1p), and epidermal growth factor receptor (EGFR) positively regulate endocrine specification (Baumgartner et al, 2014;Lof-Ohlin et al, 2017;Serafimidis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…L). To confirm that Ngn3 protein stability is regulated by the proteasome also in the context of ALI cultures, we supplemented the culture medium with 1 μM of the reversible proteasome inhibitor MG132 and confirmed that this treatment increases the number of Ngn3 + cells by twofold (Supporting Information Fig. S3H, S3I).…”
Section: Resultsmentioning
confidence: 81%
“…AMI‐5 is a xanthenyl compound that inhibits the activities of protein arginine histone methyltransferases Prmt1/3/4/6 as well as histone lysine methyltransferases (HMTases) Setd7 and Dot1l in an S‐adenosylmethionine competitive manner . Prmt1 is the most strongly expressed histone methyltransferase gene during mouse embryonic pancreas secondary transition whereas Dot1l and Setd7 are also strongly expressed during that time at significant levels (Table ) . To ensure that these proteins are present in the ES‐derived PPs as well as in the developing mouse pancreas we investigated their presence by Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation